2014
DOI: 10.1007/s11099-014-0003-3
|View full text |Cite
|
Sign up to set email alerts
|

Photosynthesis of two moss crusts from the Tengger Desert with contrasting sensitivity to supplementary UV-B radiation

Abstract: Predicting the effects of increased ultraviolet-B (UV-B) radiation due to stratospheric ozone depletion on temperate desert ecosystems requires better knowledge of the ecophysiological response of common moss species. The aim of the current work was to determine whether elevated UV-B radiation affected photosynthetic performance and chloroplast ultrastructure of two moss crusts and whether response differences were observed between the crusts. In laboratory experiments, Bryum argenteum and Didymodon vinealis, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 101 publications
1
13
0
Order By: Relevance
“…These results can be interpreted as indicating that surface soil stability (no wind erosion) is the primary factor for the colonization and development of cyanobacteria and lichens in arid sandy deserts rather than the variation of temperature and rainfall investigated in this study (Li et al, ). In addition, cyanobacteria and lichens are likely to be more tolerant of changes in temperature and rainfall because they are well adapted to drought and other extreme stresses compared with mosses (Barker, Stark, Zimpfer, Mcletchie, & Smith, ; Hui et al, ). The latter are usually distributed in microhabitats with stable and relative moist surface soils such as under shrub canopies (Kidron & Benenson, ; Li et al, ), while cyanobacteria are also found in open exposed areas and highly eroded areas (Rivera‐Aguilar, Montejano, Rodríguez‐Zaragoza, & Durán‐Díaz, ).…”
Section: Discussionmentioning
confidence: 99%
“…These results can be interpreted as indicating that surface soil stability (no wind erosion) is the primary factor for the colonization and development of cyanobacteria and lichens in arid sandy deserts rather than the variation of temperature and rainfall investigated in this study (Li et al, ). In addition, cyanobacteria and lichens are likely to be more tolerant of changes in temperature and rainfall because they are well adapted to drought and other extreme stresses compared with mosses (Barker, Stark, Zimpfer, Mcletchie, & Smith, ; Hui et al, ). The latter are usually distributed in microhabitats with stable and relative moist surface soils such as under shrub canopies (Kidron & Benenson, ; Li et al, ), while cyanobacteria are also found in open exposed areas and highly eroded areas (Rivera‐Aguilar, Montejano, Rodríguez‐Zaragoza, & Durán‐Díaz, ).…”
Section: Discussionmentioning
confidence: 99%
“…Laboratory experiments have indicated that the effects of UV-B radiation on plant photosynthetic systems are primarily in photosystem II (PS II ). Supplemental UV-B radiation may lead to the light-harvesting pigment protein complex (LH2) of PS II reversible inactivation, and this is responsible for a decreased photosynthetic rate1965. With an increase in UV-B, all the Fv/Fm, Y(II), ETR (apparent photosynthetic electron transport rate) and qP (photochemical quenching coefficient) significantly decreased.…”
Section: Discussionmentioning
confidence: 99%
“…To adapt to the extreme environment, desert bryophytes have developed strong adaptability in resistance to drought121314, extreme temperatures151617, and UV-B radiation181920. A cushion cluster of a population can enhance the water retention capacity of the capillary system by reducing the air speeds above the plant surface and decreasing the amount of water evaporation21.…”
mentioning
confidence: 99%
“…For example, soluble sugars increased in the presence of salts in desert cyanobacterial crusts . Soluble proteins, pigment, and fluorescence parameters have been found to be negatively influenced by elevated UV-B radiation in moss crusts (Hui et al 2014). These parameters might also decrease after the alleviation of N shortage in vascular plants (Zhou et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Physiological characteristics are often sensitive to environmental changes, and cryptogam species have been shown to be useful bioindicators of gradients of N pollution because their physiological parameters respond soon after the increase of atmospheric pollutants (Bignal et al 2008;Hogan et al 2010;OchoaHueso and Manrique 2011). Some physiological stress indices, such as soluble protein, soluble sugar, and free proline, have been used to test the stress response of plants and biocrust to UV, drought, and salt (Gonzalez and Pignata 1994;Hui et al 2014;Watanabe et al 2000;Wu et al 2007;Xu and Zhou 2006). N shortage on vascular plants also increases the soluble sugar and proline, and the alleviation of N limitation decreases the contents of these indices (Zhou et al 2011).…”
Section: Introductionmentioning
confidence: 99%